Improving Understanding of Intrinsic Elements of Short Stories Through the Student Teams Achievement Division (STAD) Model in Grade VI Elementary School Students - Sinta Elisa Jelita Kaunang; Alfira Anastasia Dareho; Aryanti Mundung; Julivia Kuemba; Regita Lasena; Mentari Sulu (Jurnal Multidisiplin Sahombu, 2026)
This study aims to improve sixth-grade students’ understanding of intrinsic elements in short stories through the use of the STAD cooperative learning model. The participants consisted of 21 students from SD Katolik 1 St. Yohanes Tomohon. The research employed Classroom Action Research (CAR) using the Kemmis & McTaggart model, consisting of two cycles involving planning, action, observation, and reflection. Data were collected through short story comprehension tests, observations, and documentation. The findings show an increase in students’ comprehension after applying the STAD model. Initially, students scored an average of 9 out of 10 questions. After the intervention, the average scores increased, and more students answered all questions correctly. These results indicate that the STAD model is effective in enhancing students’ understanding of intrinsic elements in short stories.